Virus-Induced Interference in Heterologously Infected HeLa Cells - Doyle, M. (1972)
In doubly infected HeLa cells, poliovirus type 1 rapidly and completely dominates vesicular stomatitis virus (VSV) plaque-forming unit production. Poliovirus type 1 shuts off incorporation of amino acids into VSV-specific proteins within 2 hr after superinfection of cells already committed to massive synthesis of VSV proteins. However, poliovirus type 1 appears to have little, if any, direct effect upon incorporation of uridine into VSV-directed ribonucleic acid (RNA) synthesis. Poliovirus apparently interferes with VSV virion production only at the level of translation of viral messenger RNA, although it interferes with host cell macromolecular syntheses at the levels of translation and transcription.